2021
DOI: 10.1111/bjd.20589
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cutaneous larva migrans over the scalp in a hod carrier

Abstract: DEAR EDITOR, An otherwise healthy daily-wage worker aged in his 40s, currently employed as a hod carrier ferrying sandbags at a construction site, presented with an extremely pruritic scalp eruption for 3 days. Examination revealed multiple follicular pustules and raised serpiginous greyish white tracts ranging from 2 to 10 cm in length spanning the vertex and temporoparietal area of scalp (a). Dermoscopy (DermLite DL4; 3Gen Inc., San Juan Capistrano, CA, USA) in polarized mode with 10 9 magnification showed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…the skin lesion in this location is characteristically raised and tortuous [11]. Another rare site of infection described in literature is the scalp [14,15]. Meotti et al reported an 11-year-old boy who presented with hair rarefaction and a serpiginous, erythematous lesion in its centre on the scalp, accompanied by intensive pruritus on the head, as well on the legs and elbows.…”
Section: Discussionmentioning
confidence: 99%
“…the skin lesion in this location is characteristically raised and tortuous [11]. Another rare site of infection described in literature is the scalp [14,15]. Meotti et al reported an 11-year-old boy who presented with hair rarefaction and a serpiginous, erythematous lesion in its centre on the scalp, accompanied by intensive pruritus on the head, as well on the legs and elbows.…”
Section: Discussionmentioning
confidence: 99%
“…In our literature review, 3 case reports were probably related to occupational contact with animals, 6 to agricultural and farm setting, one to a group of military workers and the last 2 to construction workers infected by direct contact with potentially contaminated soil or sand ( Table 1 ) [ 10 , 22 32 ]. Out of 12 reviewed cases, 7 were reported in patients living in non-endemic areas (i.e., the United Kingdom, Italy, Kosovo, South Korea, and the USA), suggesting a wide distribution of CLM.…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Other anatomical sites of CLM may be the foot, abdomen, and chest as reported in farmers, agriculturists, and construction workers also as a consequence of exposure to physical or chemical agents that may contribute to skin irritation and larva penetration [ 22 – 27 , 29 , 31 ]. However, even if the lesions are usually observed on feet and legs, they can occur on any body site in direct contact with contaminated and wet soil or sand, as showed for a hod carrier ferrying sandbags at a construction site, reporting a scalp serpiginous eruption [ 32 ]. In addition, in agricultural setting, uncommon clinical presentation can occur such as hair follicle inflammation (hookworm folliculitis), most frequently in the gluteal region, probably because larvae may be transferred to human skin through contaminated clothes, towel or other objects [ 11 ].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…It is usually caused by Ancylostoma braziliensis and Ancylostoma caninum species. The larva is trapped by forming tunnels in the epidermis for weeks or months and cannot complete its development in humans 3 …”
Section: Introductionmentioning
confidence: 99%
“…The larva is trapped by forming tunnels in the epidermis for weeks or months and cannot complete its development in humans. 3 Cutaneous larva migrans is characterized by itchy, erythematous, slightly raised, serpiginous, curved, linear, 1-4 cm long lesions, which are usually seen on the feet or buttocks. Apart from the general…”
mentioning
confidence: 99%